Corruption Traps in State Apparatus - M. Saleh Sjafei (Journal of Sumatera Sociological Indicators, 2023)
Corruption is a classic problem that exists in various countries in the world, including Indonesia. Acts of corruption in Indonesia are often carried out by state officials. This is evidenced by MaTA's analysis that in as many as 157 out of 293 corruption cases in the Banda Aceh region, state officials were involved. Corruption is carried out to enrich oneself even though there is no justification for such criminal acts. This research was conducted using a descriptive qualitative approach. Data collection was done through observation, interviews, literature study, and analysis. In this paper, it can be concluded that corruption is an act of abuse of power by officials for the purpose of enriching themselves. Corruption in Indonesia is mostly committed by state officials/corruption in any form such as extortion, fraud, trade, embezzlement, and so on, all of which are actions that cannot be tolerated. Fraud and corruption are not only undesirable, illegal, or abusive. All of these are violations of moral values that have earned fraud and corrupt practices the nicknames: "immoral" or "unethical". Corruption in Indonesia is mostly committed by state officials/corruption in any form such as extortion, fraud, trade, embezzlement, and so on, all of which are actions that cannot be tolerated. Fraud and corruption are not only undesirable, illegal, or abusive. All of these are violations of moral values that have earned fraud and corrupt practices the nicknames: "immoral" or "unethical".